2019
DOI: 10.1016/j.cmet.2018.08.022
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms Preserving Insulin Action during High Dietary Fat Intake

Abstract: Highlights d Insulin sensitivity is maintained in both men and mice with high PUFA or SFA intake d Hepatic glucose production and de novo lipogenesis are decreased with high fat intake d High fat intake decreases fasting insulin and triacylglycerol levels d High fat intake changes the plasma proteome in an immunesupporting direction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 78 publications
5
23
1
Order By: Relevance
“…Our results from mice also demonstrate a greater fat mass loss during the intake of LF diets compared with HF/HP diets. Furthermore, our results from calorie restricted HF/HP-fed mice are in agreement with the recent finding that a HF intake (64E%) for 6 weeks does not impair insulin sensitivity in healthy, slightly overweight men in caloric balance [49].…”
Section: Discussionsupporting
confidence: 92%
“…Our results from mice also demonstrate a greater fat mass loss during the intake of LF diets compared with HF/HP diets. Furthermore, our results from calorie restricted HF/HP-fed mice are in agreement with the recent finding that a HF intake (64E%) for 6 weeks does not impair insulin sensitivity in healthy, slightly overweight men in caloric balance [49].…”
Section: Discussionsupporting
confidence: 92%
“…The information about the composition of Tartary buckwheat (passed through a 80-120 mesh) used in the diet of HFDB was as follows: 2.74% rutin, 0.08% quercetin, 53.4% starch, 1.74% fiber, 16.4% protein, and 4.2% fat.Figures 1 and 2 show that after 12 weeks of high-fat feeding, the body weight, and serum TC and TG of HFD rats did not increase compared with the control group. In contrast, TC values of HFD, HFDQ, HFDR, and HFDB groups were lower than that in the control group, agreeing withLundsgaard et al, where HFD feeding lowered the TG content in mice and humans(Lundsgaard et al, 2019). HDL and LDL did not change significantly.…”
supporting
confidence: 89%
“…More recent study showed that people having diets comprised 64E% fat, 16E% protein, and 20E% carbohydrate for 6 weeks with stable body weight, insulin/glucosehomeostasis in the fasting state was changed in a non-diabetic direction, as fasting plasma insulin concentration decreased after high-fat diets. Same results were obtained by saturated and unsaturated fats 24 .…”
Section: Mellitussupporting
confidence: 77%